KEPRIBADIAN TOKOH UTAMA DALAM NASKAH MONOLOG TUA KARYA PUTU WIJAYA: KAJIAN PSIKOLOGI SASTRA - Yunia Novita Yanti (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This article aims to describe the characterizations and personalities of the main characters in Putu Wijaya's Tua monologue script. Tua monologue manuscript was chosen because this manuscript has a main character with a complex nature so that the author is interested in researching it. This type of research used in this research is qualitative research with descriptive methods. This study uses a literary psychology approach using Sigmund Freud's psychoanalytic theory and personality typology. The data source in this study is the Tua monologue by Putu Wijaya. The data collection technique used is library research or content analysis, which is to directly observe and look for the identity and description of the characters and characterizations. The data analysis technique uses flow analysis technique, which consists of three activities that occur simultaneously, namely data reduction and conclusion drawing. The results of the analysis show: (1) in the main character (Aku) there are five characteristics, namely analytical, sensitive, resigned, pessimistic and timid; (2) the impulse of the id in me is marked when he is curious about the background of the presence of a shadow that often appears and makes him anxious. Superego response is marked when the character (Aku) hopes for God's hand to help him be free from guilt. From the analysis of my personality, also found the melancholy type in (Aku).